Exploring talenting: talent management as a collective endeavour. Issue 7 (1st August 2016) - Gold, Jeff; Oldroyd, Tony; Chesters, Ed; Booth, Amanda; Waugh, Adrian
Abstract : Purpose: This paper seeks to show appreciation for the collective endeavour of work practices based on varying degrees of dependence, interdependence and mutuality between at least two people. Such dependencies have to be concerned with how talent is used and how this use is an interaction between people, a process called talenting. The aim of this paper is to provide a method to explore talenting. Design/methodology/approach: The paper provides a brief overview of recent debates relating to talent management (TM). This paper argues that TM seldom pays attention to work practices where performance is frequently a collective endeavour. A mapping method is explained to identify work practices and obtain narrative data. This paper provides a case to explore talenting in West Yorkshire Police. Findings: In total, 12 examples are found and 3 are presented showing the value of various forms of dependency to achieve outcomes. Research limitations/implications: TM needs to move beyond employment practices to work practices. There is a need to close the gap between traditional TM employment practices, usually individually focused, and work practices which are most likely to require a collective endeavour. Practical implications: There needs be ongoing appreciation of talenting to add to TM activities. Social implications: This paper recognises a more inclusive approach to TM based on work performance. Originality/value: This paper, to the best of the authors's knowledge, is probably the first enquiry of its kind.